Complications of peripheral nerve blocks - Jeng, C.L.; Torrillo, T.M.; Rosenblatt, M.A. (British journal of anaesthesia : BJA, 2010)
Complications of peripheral nerve blocks are fortunately rare, but can be devastating for both the patient and the anaesthesiologist. This review will concentrate on current knowledge about peripheral nerve injury secondary to nerve blocks, complications from continuous peripheral nerve catheter techniques, and local anaesthetic systemic toxicity.